2008
DOI: 10.1002/art.23285
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the cause of tuberculosis during tumor necrosis factor blockade

Abstract: Objective. Tumor necrosis factor (TNF) blockade increases the risk of tuberculosis (TB). The purpose of this study was to use Markov modeling to examine the contributions of reactivation of latent tuberculous infection (LTBI) and the progression of new infection withMycobacterium tuberculosis to active TB due to TNF blockade. These 2 pathogenic mechanisms cannot otherwise be readily distinguished.Methods. Monte Carlo simulation was used to represent the range of reported values for the incidence of TB associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 26 publications
3
41
0
3
Order By: Relevance
“…Despite appropriate LTBI screening, patients receiving TNF blockers are at risk for active tuberculosis due to rapid progression of a newly acquired TB infection [30]. In contrast to adults, this pathway may be predominant in children, as LTBI prevalence is supposedly lower in children than in adults.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite appropriate LTBI screening, patients receiving TNF blockers are at risk for active tuberculosis due to rapid progression of a newly acquired TB infection [30]. In contrast to adults, this pathway may be predominant in children, as LTBI prevalence is supposedly lower in children than in adults.…”
Section: Discussionmentioning
confidence: 97%
“…In adults, reactivation of latent TB infection (LTBI) seems to account for the majority of cases with a median time to onset of TB of 12-21 weeks after initiation of anti-TNF treatment [30]. There is good evidence that routine testing (and INH Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One trial of adjunctive etanercept (a soluble TNF receptor), in which patients with tuberculosis were given 25 mg twice weekly for 1 month, found etanercept to be safe and well tolerated, and there was a small benefit on sputum culture conversion and a trend towards improved chest radiography 68 . It is now recognized that etanercept is ineffective for other chronic granulomatous inflammatory conditions, such as Crohn disease and sarcoidosis 69,70 , and that it is also inefficient at reactivating LTBI (doing so at a rate estimated at 1.7% per month) 71 . These observations make it unlikely that a clinically significant benefit of etanercept would occur in larger tuberculosis trials.…”
Section: Hiv-1 Infection Profoundly Increases Tuberculosis Risk and Amentioning
confidence: 99%
“…Time to developing TB was likewise shorter with infliximab than with etanercept (1:1.7 to 1:4.6). Using Markov and Monte Carlo simulation computer models, Wallis (187) attempted to determine the respective contributions of the reactivation of latent TB versus new TB infection. He found that while both infliximab and etanercept presented high risks for new TB infection, the rate of reactivation of latent TB was 12 times higher for infliximab than for etanercept.…”
mentioning
confidence: 99%